The Role of Women in the Legislature in Aceh Tamiang - Jayanti Sari; Warjio; Indra Kesuma (Universitas Medan Area, 2023)
This study expects to determine from the Job of Ladies in the Regulative Organization of the Provincial Nation's Delegate Board of Aceh Tamiang Rule. This examination is helpful to decide the degree of the job of ladies in the council. The sort of exploration utilized is subjective examination, subjective examination is a strategy to investigate and comprehend the implying that various people or gatherings credit to social or helpful issues. The methodology utilized in this study is an unmistakable methodology. The enlightening strategy can be finished up as a technique that intends to portray or depict what is happening on the ground efficiently with realities with exact translation and interrelated information, and not exclusively to look for unadulterated fact of the matter however basically look for understanding. The consequences of this study show that ladies' support in the council in the Aceh Tamiang Rule DPRD has been executed as seen from the accompanying viewpoints: 1). APBD arranging is helped out through the phases of the APBD arranging cycle to settle on a joint choice in spending plan readiness through the proposition submitted. As well as OPD programs that are consolidated into PPAS programs. 2) The assurance of the local financial plan has been executed through legal arrangements and.3). Execution of management and arrangements of neighborhood states and local projects through Bapempeda.